Competitive exchange rate and infrastructure in a macrodynamic of economic growth - Martins Neto, Antonio Soares (2015)
We develop a dual open-economy model which incorporates infrastructure as a factor of production to investigate growth-enhancing effects of a competitive exchange rate policy under different levels of investment in infrastructure. It is suggested that a competitive exchange rate policy coordinated with an appropriate infrastructure policy should produce better results than the former policy alone. By increasing productivity in the tradable sector and by reducing inflationary pressures, this policy contributes to the success of an economic growth strategy led by a competitive currency